Connections and Feedback: Aquatic, Plant, and Soil Microbiomes in Heterogeneous and Changing Environments. (13th May 2020) - Dodds, Walter K; Zeglin, Lydia H; Ramos, Robert J; Platt, Thomas G; Pandey, Aakash; Michaels, Theo; Masigol, Mohammadali; Klompen, Anna M L; Kelly, Michelle C; Jumpponen, Ari; Hauser, Emma; Hansen, Paige M; et al.
Abstract: Plant, soil, and aquatic microbiomes interact, but scientists often study them independently. Integrating knowledge across these traditionally separate subdisciplines will generate better understanding of microbial ecological properties. Interactions among plant, soil, and aquatic microbiomes, as well as anthropogenic factors, influence important ecosystem processes, including greenhouse gas fluxes, crop production, nonnative species control, and nutrient flux from terrestrial to aquatic habitats. Terrestrial microbiomes influence nutrient retention and particle movement, thereby influencing the composition and functioning of aquatic microbiomes, which, themselves, govern water quality, and the potential for harmful algal blooms. Understanding how microbiomes drive links among terrestrial (plant and soil) and aquatic habitats will inform management decisions influencing ecosystem services. In the present article, we synthesize knowledge of microbiomes from traditionally disparate fields and how they mediate connections across physically separated systems. We identify knowledge gaps currently limiting our abilities to actualize microbiome management approaches for addressing environmental problems and optimize ecosystem services.